2002
DOI: 10.1046/j.1526-4610.2002.02124.x
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Daily Headache in Children and Adolescents Presenting to Tertiary Headache Clinics

Abstract: Our data suggest that rather than having two coexistent headache types, children and adolescents with chronic daily headache have a single syndrome that, in many cases, will paroxysmally worsen and gather migrainous features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
1
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 46 publications
6
87
1
4
Order By: Relevance
“…Thus, further studies should focus on the relationship between TMD and TTH. In another clinic-based study, findings were similar to ours 29 .…”
Section: Discussionsupporting
confidence: 88%
“…Thus, further studies should focus on the relationship between TMD and TTH. In another clinic-based study, findings were similar to ours 29 .…”
Section: Discussionsupporting
confidence: 88%
“…1,[6][7][8]11,12,17,18,20 In a community based study of 12 to 14-year-old school children, almost half of the 121 subjects with CDH had at least one psychiatric disorder; depressive disorders were found in 30% (36 of 121) and anxiety disorders in 36% (43 of 121); additionally 20% (24 of 121) had high "current" suicidal scores. 18 These figures were much higher than those in the age matched general population.…”
Section: Anxiety and Depressive Disordersmentioning
confidence: 99%
“…Transformation occurred in 78% of 630 patients in the series of Mathew et al 35 A similar percentage has been reported in children. 6,8,10,20 Chronic migraine, CTTH, mixed CM and CTTH, in variable proportion, have constituted the most frequent subtypes of primary CDH in clinic based studies. 3,[5][6][7][8][9][10][11][12]16,19,20 In an adolescent community based study, the relative frequencies for CM and CTTH were 7% and 66% respectively (N=122) but 59% of those with CTTH also had migraine attacks.…”
Section: Primary Subtypes (Codes 1-4)mentioning
confidence: 99%
“…Of these patients, NDPH is diagnosed more frequently in children and adolescents than in adults [6]. NDPH has been estimated to occur in 1.7% to 10.8% of adults with CDH [14,15], and in 13% to 35% of children with CDH [16][17][18]. It is more common in females, with the female/male ratio in adults at 2.5:1 [5] and in children and adolescents at 1.8:1 [4•].…”
Section: Epidemiologymentioning
confidence: 99%